SERANGAN HAMA PENGGEREK BATANG CENGKEH Hexamithodera semivelutina Hell. DI DESA KUMELEMBUAI KABUPATEN MINAHASA SELATAN - Gladys M. Tumanduk; Betsy A.N. Pinaria; Christina L. Salaki (Universitas Sam Ratulangi, 2017)
ABSTRACKCloves (Syzigium aromaticum. L) is a cash crop that has a high economic value in Indonesia. One type of plant pests that attack plants clove is the clove stem borer (H. semivelutina).The study aims to determine the clove stem borer attack in the village of Kumelembuai. The research was carried on in the village Kumelembuai for 3 months from October to December 2016. The research was conducted by survey method. Samples were observed total 15 trees randomly selected plants. Observations were made 2 weeks for 3 months. Things are observed number of trees and the number of hoist stem borer are active and which are inactive and the percentage of stem borer attack cloves begin the first observations until the sixth observation. The results showed there were 13 trees affected with 55 holes hoist pests which are no longer active in the garden Wukir, in the garden there are 11 trees affected Maruasey and 43 holes that are no longer active. The highest percentage of attacks seen in the garden Wukir by 73.33% compared with the number of attacks in the garden Maruasey percentage with 33.33% total percentage of attacks.